Spectroscopic investigation and thermal behavior of new carbonyl complexes [M(CO)(4)(N-N)(CuX)], (M = W, Mo; N-N=2,2 '-bipyridine, 1,10-phenanthroline; X = Cl, SCN) - Haddad, P. S.; Mauro, A. E.; Nogueira, V. M.; Klein, S. I. (Kluwer Academic Publ, 2003)
M(CO)(4)(N-N)] reacts with CuCl to give new heterobimetallic metal carbonyls of the type [M(CO)(4)(N-N)(CuCl)], M = W, Mo; N-N = 2,2'-bipyridine (bipy), 1,10-phenanthroline (phen). Reactions of [M(CO)(4)(N-N)(CuCl)] with NaSCN produced the series of complexes of general formula [M(CO)(4)(N-N)(CuSCN)]. The i.r. spectral of all the bimetallic carbonyls exhibited the general four m ( CO) band patterns of the precursors. The u.v.-vis. spectral data for precursors and products showed bands associated with pi --> pi* (nitrogen ligands), d-->d (intrametal), as well as MLCT d-->pi* (nitrogen ligands) and MLCT d --> pi*(CO) transitions. The [M(CO)(4)(N-N)(CuX)] (X = Cl, SCN) emission spectra showed only one band associated with the MLCT transition. The t.g. curves revealed a stepwise loss of CO groups. The initial decomposition temperatures of the [M(CO)(4)(N-N)(CuX)] series suggest that the bimetallic compounds are indeed thermally less stable than their precursors, and the X- ray data showed the formation of MO3, CuMO4, Cu2O and CuO as final decomposition products, M = W, Mo. The spectroscopic data suggests that the heterobimetallic compounds are polymeric.